Diarrhea in Neonatal Calves - Bacterial and Viral Factors - Öztrürk, Dilek; Kale, Mehmet; Şahan Yapıcıer, Özlem; Sait Saltık, Hasbi; Atlı, Kamil; Yaman, Sibel (Acta Scientiae Veterinariae, 2024)
Background: Neonatal calf diarrhea is one of the most important problems of calf breeding in the world. It causes serious economic losses by causing deaths in calves in the 1st 10 days of their lives. Although many factors cause calf diarrhea, Escherichia coli (E. coli), Salmonella spp., Campylobacter spp., viral agents such as Bovine Rotavirus (BRV) and Bovine Coronavirus (BCoV) and parasitic agents such as Cryptosporidium spp., Eimeria spp. and Toxocara spp. frequently plays a role in calf diarrhea. In addition to these infectious factors, the formation of diarrhea has been linked to a number of other factors, including unfavorable barn conditions, mass rearing, inadequate cleaning and disinfection of barn tools, delaying the feeding of colostrum to newborn calves, failing to do so, and failing to disinfect the umbilical cord after delivery. The identification of the microorganisms and virulence factors responsible for diarrhea in newborn calves will direct the development of preventative measures and control strategies. The present study aimed to determine various virulence factors (Stx1, Stx2, STa, eaeA, K99 and F41) of Escherichia coli isolated from fecal samples and to investigate the prevalence of BRV, BCoV and E. coli K99 agents which play a role in the etiology of neonatal calf diarrhea in Burdur province. Materials, Methods & Results: This study was carried out in 75 different cattle farms with diarrhea problem in Burdur province and its districts. Rectal swab samples were taken from 90 calves with diarrhea between 0-4 weeks of age, using 2 sterile swabs from each animal. The swabs are used for the detection of BRV, BCoV and E. coli K99 by direct ELISA, and the isolation of E. coli. The swabs were cultured on blood agar including 7% sheep blood and MacConkey agar. The isolated bacteria were identified by conventional bacteriological culture methods such as Gram staining, triple tube method, oxidase. The bacteria isolated and identified as E. coli were stored at -20 ºC by using. Enzyme immunobinding assay (ELISA) was positive in 45 of the calf fecal samples. BRV was detected in 28 (31.11%) of samples, BCoV in 15 (16.67%) and E. coli K99 in 11 (12.22%) samples by ELISA. While BRV and BCoV were detected together in 5.56% of the samples, BRV and E. coli K99 were detected in 1.11% of samples, BCoV, E. coli K99 were detected in 1.11% of samples and all three infections were detected together in 1.11% of samples. The virulence factors of E. coli was investigated by polymerase chain reaction (PCR) and Stx1, K99, F41 and eaeA virulence genes were determined in 2, 5, 3, 4 of samples, respectively. K99 and F41 antigens were detected together only in 2 of the E. coli isolates. The according to ages, it was determined that the highest BRV was detected between 1-7 days of age and 8-15 days of age. While E. coli was detected in 5 of 1-day-old calves, BCoV was also detected in 1 of these calves. Discussion: In this study, it has been determined that neonatal calf diarrhea is mostly caused by BRV in Burdur province, followed by BCoV and E. coli. Even though E. coli was recovered from the samples, the inability to extract virulence factors suggests that additional virulence factors might potentially be involved in the infection. It was concluded that the determination of virulence factors of E. coli isolates can be a guide in the preparation of protection and control strategies in calf diarrhea. Keywords: calf diarrhea, bovine coronavirus, E. coli, bovine rotavirus, ELISA, PCR.